Novel Role Of DSNB in Staging of Primary Urethral Cancer: New Standard? - Adnan Fazili; R. Barry Sirard; Laura Elst; Kaat Vandermaesen; Hongzhi Xu; Maarten Albersen; Philippe E. Spiess (International Brazilian Journal of Urology)
ABSTRACT We describe the novel use of dynamic sentinel node biopsy (DSNB) in five patients with primary urethral squamous cell carcinoma (U-SCC) and no evidence of inguinal node disease across two centers in North America and Europe between 03/2021 and 06/2024. Each of these referral centers sees over 75 cases of penile cancer per year and approximately 10 cases of U-SCC per year. Patients underwent DSNB concomitant to surgical resection of the primary tumor (n=3), or in a deferred manner (n=2), six weeks after primary surgery. In the five DSNBs performed, clinically occult nodal metastasis was discovered in one patient. In this patient DSNB was performed after local recurrence and repeat imaging confirming cN0 status. Only one minor complication with DSNB was observed. Awaiting further investigations in larger series, this study highlights the feasibility of DSNB in primary U-SCC with clinically node negative disease.